2019
DOI: 10.1108/ijshe-01-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Bottled water versus tap water

Abstract: Purpose Bottled water consumption continues to break records worldwide and its environmental impact is often underestimated by the consumer. Many factors affect individuals’ choices to consume tap water and bottled water including perceived health risks and water quality. The University of South Florida (USF) has joined a nationwide initiative to become carbon-neutral, and reducing bottled water consumption was a chosen strategy. The purpose of this study was to assess the risk perceptions and drinking water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…Beyond these general drivers, it is important to shed light on how multiple socio-demographic and political factors, including age, gender, income, education, ethnicity, age, political ideology, the number of children in their household, previous experience, place of residence, and trust in the government affect the perception and preference of consumers towards bottled water [15]. For instance, on average ethnic minorities in developed countries tend to consume more bottled water than the general population [23,24]. In this regard, a study in the USA found that minority children drank three times more bottled water than non-minority children [25] (see also [16]).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond these general drivers, it is important to shed light on how multiple socio-demographic and political factors, including age, gender, income, education, ethnicity, age, political ideology, the number of children in their household, previous experience, place of residence, and trust in the government affect the perception and preference of consumers towards bottled water [15]. For instance, on average ethnic minorities in developed countries tend to consume more bottled water than the general population [23,24]. In this regard, a study in the USA found that minority children drank three times more bottled water than non-minority children [25] (see also [16]).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, taste and health beliefs stand out as the most prominent (Ballantine et al, 2019; Doria, 2006; Levêque and Burns, 2018; March et al, 2020; Qian, 2018; Ward et al, 2009). In addition, sociodemographic characteristics are related to consumers’ water-intake decisions (Graydon et al, 2019; Saylor et al, 2011). Concerning safety, tap water may not be safe in certain countries (Pant et al, 2016); nevertheless, previous authors proved that tap water is safe in many other countries.…”
Section: Related Literaturementioning
confidence: 99%
“…A similar study was carried out in a university of Florida, some differences were identified between non-consumers and heavy consumers of bottled water, such as taste, convenience and the belief that bottled water is a safer source are drivers of bottled water consumption. In addition, some of the participants recognized some of the benefits of tap water, in particular those related to its price, its environmental impact (less than that of bottled water) and the convenience of having filling stations at campus (Graydon et al 2019). Also, norms, peer behavior, and perceived health benefits were found to be linked to purchase intention (Xu & Lin 2018).…”
Section: Introductionmentioning
confidence: 99%